LAW ENFORCEMENT AGAINST VIOLATIONS OF FREEDOM OF EXPRESSION IN PUBLIC (STUDY AT THE LABUHAN BATU POLICE): PENEGAKAN HUKUM TERHADAP PELANGGARAN KEBEBASAN MENYAMPAIKAN PENDAPAT DI MUKA UMUM (STUDI DI POLRES LABUHAN BATU) - Rijaldi Rijaldi; Isnaini Isnaini; Wenggedes Frensh (SOSIOEDUKASI, 2026)
Freedom of expression in public is a fundamental pillar in a democratic state guaranteed by the Indonesian constitution, particularly Article 28E paragraph (3) of the 1945 Constitution of the Republic of Indonesia and further regulated in Law Number 9 of 1998. However, in practice, law enforcement against violations of this right is often colored by complexity and challenges. Based on this, the formulation of the problem of this study is first, What are the legal regulations regarding violations of freedom of expression in public at the Labuhan Batu Police?, Second, What is the mechanism for law enforcement against violations of freedom of expression in public at the Labuhan Batu Police?; and Third, What factors are the obstacles and supporters in law enforcement against violations of freedom of expression in public at the Labuhan Batu Police?. The method used in this research is empirical legal research with a conceptual approach and statutory regulations. Data collection techniques are through observation, interviews and documentation studies with qualitative descriptive data analysis. The results of this study indicate that. First, related to legal regulations, namely the 1945 Constitution of the Republic of Indonesia and Law No. 9/1998 concerning Freedom of Expression in Public, Law (UU) Number 1 of 1946 concerning Regulations on Criminal Law, Law No. 11 of 2008, revised to Law No. 19 of 2016 concerning the Law on Information and Electronic Transactions and Regulation of the Chief of Police of the Republic of Indonesia No. 7 of 2012 concerning Procedures for organizing services, securing and handling security cases of expressing opinions in public. Second, the law enforcement mechanism is multi-layered, from pre-action to enforcement, with the Police Standard Operating Procedures (SOPs) as the primary guideline. Third, inhibiting factors include uneven human resource capacity in understanding human rights, the existence of ambiguous articles, political intervention, and a repressive legal culture. Supporting factors include the constitutional basis of the 1955 Constitution and Law No. 9/1998 as the legal basis.